Saccharin and tert-Butyl Nitrite: Cheap and Efficient Reagents for the Synthesis of 1,2,3-Benzotriazine-4-(3H)-ones from 2-Aminobenzamides under Metal-Free Conditions - Khaligh, Nader Ghaffari; Johan, Mohd Rafie; Juan, Joon Ching (CSIRO Publishing, 2018)
A mild and eco-friendly protocol for the synthesis of 1,2,3-benzotriazine-4-(3H)-ones is described using saccharin as a cheap and efficient catalyst and tert-butyl nitrite as a diazotization reagent for the first time. The current method has advantages such as cost effectiveness, energy efficiency, and simple experimental procedure, good yield of the desired product, and metal-free and environmentally benign conditions.